Education Expenditure and Economic Growth of GCC Countries: New Evidence from Panel ARDL and Wavelet Coherence Approaches - Zaki Ahmad; Mahvish Nawaz Mokal (International Journal Labs, 2026)
The nexus between educational, research and development expenditures and economic growth represents a salient principal point within the practical realm of empirical investigations. This paper focuses on the long- and short-run relationship between government expenditure in education, research and development and economic growth in Gulf Cooperation Council (GCC) countries from 1998-2021. Using panel autoregressive distributed lag (ARDL) models, the result confirms that government education expenditure (EDE) is positively associated with economic growth in the long run as well as in the short run. Furthermore, research and development (R & D) is positively significant in the long run; however, it is insignificant in the short run with economic growth. The policy implications of the result highlight the importance of sustained investment in education, research and development to advance economic growth. Policymakers should adopt a balanced and forward-looking approach, recognising the significance of these investments for both short-term and long-term economic prosperity.